Introduction of a New Locking Nail for Treatment of Intraarticular Calcaneal Fractures. Issue 3 (March 2016) - Zwipp, Hans; Paša, Libor; Žilka, Luboš; Amlang, Michael; Rammelt, Stefan; Pompach, Martin
Abstract : Objectives: To reduce the complication rate associated with open reduction and internal fixation of displaced intraarticular calcaneal fractures through extensile approaches, a locking nail system (C-Nail) was developed for internal fixation. Design: Prospective case–control study. Setting: Two level I trauma centers (university hospital) and 1 large regional hospital in the Czech Republic and Germany. Patients: One hundred three patients (89 male and 14 female; mean age, 45.6 years) with 106 calcaneal fractures were treated between February 2011 and October 2013. Intervention: In all 106 cases, the stainless steel C-Nail with a length of 65 mm, a diameter of 8 mm, and 7 locking options was used for internal fixation. Previous reduction of the posterior facet was performed in 15 cases percutaneously, assisted by arthroscopy and fluoroscopy, and in 91 cases by a sinus tarsi approach. The reduced joint surface was fixed by 1 or 2 compression screws. All other fragments were fixed after reduction and temporary K-wire fixation with the C-Nail introduced percutaneously through the tuberosity and 5 to 6 interlocking screws. The latter were introduced into the sustentacular, the tuberosity, and the anterior process fragments with an aiming device consisting of 3 arms. Main Outcome Measures: Patients were assessed for complications, restoration of Böhler angle, posterior facet reduction with postoperative computed tomography, and weight-bearing radiographs at 6 months. Functional outcome was assessed using the American Orthopaedic Foot & Ankle Society (AOFAS) ankle/hindfoot scale after 6 and 12 months for all patients. Results: Wound edge necrosis was seen in 2 cases (1.9%), and soft tissue infection was observed in 1 case (0.9%). Böhler angle improved from 7.3 degree preoperatively to 28.7 degree at 6 months. The posterior facet step-off was reduced from 5.3 mm preoperatively to 0.7 mm postoperatively. The average AOFAS score averaged 89.5 at 6-month and 92.6 at 12-month follow-up. Conclusions: The C-Nail is a new locking system for treatment of displaced intraarticular calcaneal fractures combining a primary stability with reduced soft tissue complications. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.